LAMA MENDERITA DENGAN KUALITAS HIDUP PASIEN PPOK - Asni Hasaini (LPPM Universitas Sari Mulia, 2020)
Background: The number of COPD cases is estimated to be ranked third as the most common cause of death in middle-income countries. The most dominant symptom is shortness so that it can affect social activities that negatively impact the quality of life. Quality of life can decrease with the severity and duration of the patient's diagnosis. Objective: To analyze the relationship between duration of suffering and the quality of life of COPD patients at Ratu Zalecha Martapura. Method: This type of quantitative correlation study with a cross-sectional approach with a sample of 104 COPD patients in Ratu Zalecha Martapura Regional Hospital using Consecutive Sampling. Research instruments using questionnaires and for quality of life using the Saint George Respiratory Questionnaire Chronic Obstructive Pulmonary Disease (SGRQ-COPD) and data analysis using Spearman Rho. Results: There is a relationship between the duration of suffering and the quality of life of COPD patients at Ratu Zalecha Martapura with a value of ρ value = 0.002 and rho value = 0.294. Conclusion: The length of time suffered by the majority of COPD patients in the old category ≥ 3 years by 59.6%, the quality of life of the majority of COPD patients in the poor category by 75%. There is a relationship between the duration of suffering and the quality of life of COPD patients in Ratu Zalecha Martapura with a value of ρ value = 0.002 (ρ value <0.05) and rho value = 0.294. Latar Belakang: Jumlah kasus PPOK diperkirakan menjadi peringkat ketiga sebagai penyebab kematian tersering di negara berpenghasilan menengah. Gejala yang paling dominan adalah sesak sehingga dapat mempengaruhi aktivitas sosial yg berdampak negative terhadap kualitas hidup. Kualitas hidup dapat menurun sejalan dengan tingkat keparahan dan lama pasien didiagnosis penyakit. Tujuan: Untuk menganalisis hubungan antara Lama menderita dan Kualitas Hidup Pasien PPOK di Ratu Zalecha Martapura. Metode: Jenis Penelitian kuantitatif korelasi dengan pendekatan cross sectional dengan sampel penelitian sebanyak 104 pasien PPOK di RSUD Ratu Zalecha Martapura dengan menggunakan Consecutive Sampling. Instrumen penelitian menggunakan kuesioner dan untuk kualitas hidup menggunakan Saint George Respiratory Questionnare Chronic Obstructive Pulmonary Disease (SGRQ-COPD) dan analisis data menggunakan Spearmans Rho. Hasil: Ada hubungan antara Lama menderita dan Kualitas Hidup Pasien PPOK di Ratu Zalecha Martapura dengan nilai ρ value = 0,002 dan nilai rho = 0,294. Kesimpulan: Lama Menderita Pasien PPOK mayoritas dalam kategori lama ≥ 3 tahun) sebesar 59,6%, Kualitas Hidup Pasien PPOK mayoritas dalam kategori buruk sebesar 75%. Ada hubungan antara Lama menderita dan Kualitas Hidup Pasien PPOK di Ratu Zalecha Martapura dengan nilai ρ value = 0,002 (ρ value <0,05) dan nilai rho = 0,294.